2021
DOI: 10.1089/jchc.18.09.0048
|View full text |Cite
|
Sign up to set email alerts
|

Audit of a Mindfulness-Based Cognitive Therapy Course Within a Prison

Abstract: This article examines the effectiveness of the Eight week Mindfulness Based CognitiveTherapy course for Depression within the prison population. Prisons see higher rates of mental ill health across the spectrum and we were interested to see how a manualised mindfulness approach to treating depression, a major cause of ill health, would affect this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Levels of psychological acceptance increased (Malouf et al , 2017). One study further found self-perceived improvements in health and reductions in physical body complaints, such as pain (Maroney et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Levels of psychological acceptance increased (Malouf et al , 2017). One study further found self-perceived improvements in health and reductions in physical body complaints, such as pain (Maroney et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Involving both formal and informal mindfulness practices, MBCT aims to gradually increase participant self-awareness, starting with neutral content (such as bodily sensations) and working towards awareness of one’s thoughts (Segal et al , 2019). MBCT has been implemented within prisons with some success (An et al , 2019b; Maroney et al , 2021; Xu et al , 2016) and typically takes place via 8 weekly 2–2.5 h sessions and frequently involves homework, as well as a day-long retreat.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations